Harnessing Regional Trade Agreements as Catalysts for Climate-Smart Trade: The Case of Western Balkans Countries - Kocev, Ljuben; Toshevska Trpchevska, Katerina; Tonovska, Jasna (Association of Economists and Managers of the Balkans – UdEkoM Balkan, 2023)
The concept of climate-smart trade is gaining momentum as trade agreements increasingly incorporate provisions to balance economic growth and environmental conservation. While in the past, environmental and climate issues played a minor role in international trade agreements, recently there has been a growing trend towards incorporating climate-smart provisions, particularly in regional trade agreements (RTAs). These provisions aim to promote sustainable development, pursue international environmental goals, ensure a level playing field, and enhance environmental cooperation. The paper analyzes the emergence of environmental and climate-related provisions in free trade agreements. It attempts to define them, explain how they are incorporated into free trade agreements, and assess the reasons for the increased number of such provisions. The paper then briefly analyses statistical data related to the types of environmental and climate-related provisions contained in FTAs, before going into details of the climate-smart provisions of the regional trade agreements in the Western Balkans.
Keywords: Climate-smart trade; Environmental provisions; Regional trade agreements; Western Balkans